Proposals for a new order for the commodity markets - Richard Senti (Intereconomics, 1977)
The following article pinpoints the elements of a possible new order for the commodity markets against the background of the existing market order for raw materials and proposals for its reform which have been made public. The existing order is briefly reviewed in the first part of the article while topical reform proposals are set out in the second part. The direction in which the search for a new international market order for raw materials should point so as to accommodate the various, often sharply diverging expectations and demands of the trading partners is indicated in the final part.
Keywords: 330; Raw Materials